(untitled) (Jurnal De Jure Muhammadiyah Cirebon, 2024)
This research analyzes the juridical points of convergence between Islamic Law and Civil Law in the territorial mapping of agreements, particularly in the context of the termination of obligations. By detailing fundamental concepts such as performance fulfillment, debt restructuring, compensation, debt release, cancellation, and lapse of time, this study demonstrates substantial similarities between the two legal systems. These points of convergence establish a solid legal foundation for the integration of laws, with philosophical relevance and a response to societal needs for legal certainty. The alignment of applicable laws with the values and norms of society is crucial in achieving the desired legal certainty. This legal integration not only reflects harmony between Islamic Law and Civil Law but also provides a basis for holistic and responsive regulations in the face of modern societal dynamics. The synergy between these legal systems creates a robust foundation for harmonization within the national legal framework, recognizing and incorporating legal principles to achieve justice and legal certainty for the community. Keywords: Juridical Points of Convergence; Islamic La;, Civil Law.